Certainty and Doubt in Islamic Religious Education toward a Dialogue between Islamic and Cartesian Epistemology - Fathurrohman, Rizal (Eshraq: Journal of Islamic Studies, 2026)
This study explores the epistemological relationship between certainty and doubt in Islamic Religious Education through a philosophical dialogue between Islamic and Cartesian epistemology. The problem of knowledge in education concerns how certainty is attained, justified, and internalized within the learning process. In Islamic epistemology, certainty is expressed through the concept of yaqīn, which integrates revelation, rational reflection, and spiritual intuition as interconnected sources of valid knowledge. Conversely, Cartesian epistemology begins with methodological doubt as a critical foundation for establishing indubitable certainty grounded in rational self awareness. This study employs a qualitative philosophical approach using conceptual and epistemological analysis, drawing on the epistemological perspectives of Abu Hamid al-Ghazali and Rene Descartes. The findings demonstrate that doubt and certainty function as complementary epistemic processes rather than contradictory states. Doubt serves as a methodological tool to examine the limits and validity of knowledge, while certainty represents the culmination of rational inquiry and spiritual realization. This epistemological dialogue contributes to reconstructing the philosophical foundation of Islamic Religious Education by integrating rational and spiritual modes of knowing, thereby enhancing its epistemic legitimacy, intellectual depth, and transformative educational purpose.